PENERAPAN METODE K-MEANS CLUSTERING UNTUK MENENTUKAN CALON MAHASISWA BERPRESTASI - Ananda, Lidya Rizki (Jurnal Inovasi Teknik Informatika, 2018)
It takes such a long time to choose a prospective student achiever. Since the support software has been developed in data processing and presentation of information. On of the ways to solve the problem is by using data mining. Aplicating data mining aims to speed up the process of decision making, which university used to process the student data manually. Data mining is combined with clustering methode by using K-Means algorithm can make the process easier to choose a prospective student achiever, then become a new knowledge and more competitive like for Akademi Manajemen Gunung Leuser Palas Sumatera Sumatera Utara. Keywords : Data Mining, K-means Algorithm, Clustering